Pelatihan Penyusunan Paket Wisata Bagi Masyarakat Sadar Wisata di Desa Sibetan, Kecamatan Bebandem, Kabupaten Karangasem - Rahjasa, Putu Surya Laksana; Wijayanti, Ni Putu Evi; Darmiati, Made; Rahadiarta , I Gede Ngurah Primanda S (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2024)
The potential of a tourist village that is not well packaged will certainly be difficult to promote as a tourist attraction. Sibetan Village actually has a variety of potential that can be "sold" to tourists, but the lack of community knowledge in identifying and packaging this potential is an obstacle expressed by the people of Sibetan tourist village. Seeing the need to develop the quality of human resources in Sibetan village, it was deemed necessary to carry out training with a focus on preparing tour packages for tourism-aware communities in Sibetan village, Karangasem Regency, which was carried out by the D4 Travel Business Study Program, Bali Tourism Polytechnic as a form of service to the community. The result of the implementation of this training is a change in the understanding of the training participants in recognizing the potential of the Sibetan tourist village and being able to package this potential into an attractive tourist attraction.